Efektivitas Biaya Konseling Apoteker Pada Pasien Program Pengelolaan Penyakit Kronis Diabetes Melitus Tipe 2 - Fajriansyah Fajriansyah; Keri Lestari; Irma Melyani Puspitasari; Aulia Iskandarsyah (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Type 2 Diabetes Mellitus (T2DM) imposes a substantial economic burden on healthcare systems. Evidence indicates that pharmacist involvement in medication management can improve glycemic control, adherence, quality of life, and reduce drug-related problems. However, the cost-effectiveness of pharmacist participation within the Prolanis program remains unclear. This study aimed to evaluate the cost-effectiveness of pharmacist counseling in managing T2DM under the Prolanis scheme compared with standard care. A cluster randomized clinical trial was conducted from 2017 to 2018 across four primary health centers in Makassar City. Eligible patients were allocated to an intervention group receiving structured pharmacist counseling or a control group receiving standard Prolanis services. Economic evaluation was performed from the payer and healthcare provider perspectives. A total of 220 patients met the inclusion criteria (109 intervention, 111 control). In the control group, the Average Cost-Effectiveness Ratio (ACER) based on direct medical costs was IDR –1.852.391,24 per 1% HbA1c reduction and IDR –9.725.054 per 1-point MMAS-8 improvement. Under capitation costs, ACERs were IDR –14.285,71 and IDR –75,000. In the intervention group, ACERs for direct medical costs were IDR 1.632.355,45 per 1% HbA1c reduction and IDR 1.300.783,25 per MMAS-8 point increase; for capitation costs, ACERs were IDR 11.764,71 and IDR 9.375. Cost-effectiveness mapping showed the intervention group in Quadrant II, indicating improved effectiveness with acceptable incremental costs. These findings support the economic value of integrating pharmacist counseling into Prolanis T2DM management.